Lixeira de Parintins: segregados ou agregados? - Vieira, Girleno Barros (Brasil, 2024)
This report describes the production process of the documentary “Lixeira de Parintins: segregados ou aggregados”, in which the situation experienced by hundreds of families living near the Lixeira is highlighted. The city of Parintins already had two other areas for garbage disposal. Currently, the Parintins Waste Bin, today called Controlled Landfill, as a result of the latest initiatives promoted by the City Hall for waste treatment, continues to be an unsolved problem. In this documentary, we chose to use the term Dumpster due to the lack of operational aspects consistent with the assumptions in the National Solid Waste Policy. The documentary exposes reports of people who suffer directly from the impacts of the lack of proper treatment of waste generated in the city. Given the complexity of its theme, the research is of a basic nature, carried out through a Case Study, which aimed to produce an expository documentary, having Nichols (2016) as a theoretical assumption, with 5 residents and 4 public agents whose activities are directly or indirectly related to the impacts of the Parintins dump. For this, it opted for direct observation and semi-structured interview as a research technique and technical instrument for the elaboration of the final product. Finally, the documentary shows the families who live close to Lixeira and who are living in a context of social, environmental and health vulnerability. It also shows that actions by the Government need to be improved and that the National Solid Waste Policy requires implementation in terms of proper disposal of waste.